The Effect Analysis Risk of Credit, Liquidity and Capital on Banking Profitability (Global Journal of Management and Business Research, 2018)
This study aims to examine the effect of credit risk, liquidity and capital on the profitability of commercial banks. Type of causal research (Causal Study) with sampling using the method of Purposive Sampling. Sampling is conducted at commercial banks (Private, corporate, foreign and non-foreign exchange) listed on the Jakarta Stock Exchange for the period 2012-2016. The research method used is panel data regression analysis with Eviews version 9.0 as a statistical test tool. The test results show credit risk, liquidity risk and capital effect on profitability collectively (simultaneously). Partially, credit risk and capital have an effect on profitability, while liquidity risk has no effect to profitability.
Keywords: non performance loan (NPL); loan to deposit ratio (LDR); capital adequacy ratio (CAR); return on assets (ROA)